2023
DOI: 10.18388/abp.2020_6602
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum stress involves the high glucose-induced nucleus pulposus cell pyroptosis

Abstract: Objective: Diabetes has been identified as a risk factor for intervertebral disc degeneration (IDD). The aim of this study is to investigate the potential mechanism underlying diabetes-related pyroptosis in nucleus pulposus (NP) cells. Methods: We used a high-glucose environment to mimic diabetes in vitro and examined the endoplasmic reticulum stress (ERS) and pyroptotic response. Furthermore, we utilized activators and inducers of ERS to explore the role of ERS in high-glucose-induced pyroptosis in NP cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“… 23 A preclinical study found that injecting bone marrow-derived macrophages into herniated discs reduced the size of the herniation by 44%, suggesting that macrophages promote resorption of herniated discs, which could be an effective clinical therapy. 53 In addition, chemokines, 54 miRNAs, 55 cell pyroptosis, 56 endoplasmic reticulum stress, 57 oxidative responses, 58 and lipid metabolism 59 are all important pathways through which immune cells mediate IDD. Only a refined understanding of the role of immune cells in IDD will allow further strategies and protocols to be developed for later treatment.…”
Section: Mechanisms Of Immune Cells In Iddmentioning
confidence: 99%
“… 23 A preclinical study found that injecting bone marrow-derived macrophages into herniated discs reduced the size of the herniation by 44%, suggesting that macrophages promote resorption of herniated discs, which could be an effective clinical therapy. 53 In addition, chemokines, 54 miRNAs, 55 cell pyroptosis, 56 endoplasmic reticulum stress, 57 oxidative responses, 58 and lipid metabolism 59 are all important pathways through which immune cells mediate IDD. Only a refined understanding of the role of immune cells in IDD will allow further strategies and protocols to be developed for later treatment.…”
Section: Mechanisms Of Immune Cells In Iddmentioning
confidence: 99%